2024
DOI: 10.3344/kjp.23344
|View full text |Cite
|
Sign up to set email alerts
|

Cooled radiofrequency ablation of genicular nerves for knee osteoarthritis

Myong-Hwan Karm,
Hyun-Jung Kwon,
Chan-Sik Kim
et al.

Abstract: Knee osteoarthritis (OA) is a prevalent and debilitating musculoskeletal condition that significantly affects the quality of life of millions of individuals worldwide. In recent years, cooled radiofrequency ablation (CRFA) has become a viable treatment option for knee OA. This review thoroughly evaluated the existing literature on CRFA therapy for knee OA. It delved into the mechanisms behind CRFA, evaluated its clinical efficacy, and investigated potential avenues for future research and application. The insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Since the first case report on the effectiveness of cooled RFA in patients with chronic knee pain [ 14 ], prospective and retrospective studies have been conducted to confirm the efficacy of the cooled RFA of genicular nerves in patients with chronic knee pain due to OA [ 8 ]. These studies have demonstrated that the cooled RFA of genicular nerves provides notable pain relief, improved functional outcomes, and positive patient-reported experiences in patients with chronic knee pain [ 8 ]. Moreover, recent prospective studies observed sustained significant pain relief for up to two years in approximately half of the patients who underwent this procedure [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first case report on the effectiveness of cooled RFA in patients with chronic knee pain [ 14 ], prospective and retrospective studies have been conducted to confirm the efficacy of the cooled RFA of genicular nerves in patients with chronic knee pain due to OA [ 8 ]. These studies have demonstrated that the cooled RFA of genicular nerves provides notable pain relief, improved functional outcomes, and positive patient-reported experiences in patients with chronic knee pain [ 8 ]. Moreover, recent prospective studies observed sustained significant pain relief for up to two years in approximately half of the patients who underwent this procedure [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cooling mechanism is designed to minimize damage to adjacent structures and increase the size of lesions, which may enhance the safety and efficacy of the RFA treatment; these features have led to the growing application of cooled RFA on genicular neurotomy [ 6 , 7 ]. Furthermore, there is increasing evidence that supports the clinical efficacy of cooled RFA targeting genicular nerves for knee OA [ 8 ]. Nevertheless, no study has been conducted to eliminate the potential influence of a placebo effect associated with this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, radiofrequency ablation (CRFA) has emerged as a promising alternative treatment modality for KOA. In contrast to conventional radiofrequency procedures, CRFA employs advanced cooling technology to target and modulate sensory nerves responsible for pain signal transmission [8].…”
Section: Introductionmentioning
confidence: 99%